Implementasi Rencana Tata Ruang Wilayah Kota Semarang - Cahyo Adhi Widodo; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Urban Land use Plan of Semarang need to be studied further to see location of demographic Semarang City which make Semarang City developed become city that focusing on trade and service, and density of population of Semarang City which increasingly dense every year, in order to make Semarang City as center of international trade and service that is safe, convenient, productive, and sustainable. However, various strategic issues that developed are the high land conversion, the illegal construction of illegal buildings and the placement of development status that is not in accordance with the spatial layout of Semarang City Government, as happened in Genuk Subdistrict, the development of industrial number in Genuk resulted in the increasing of industrial activity that have impact on environmental quality, industrial pollution cases can also be attributed to a lack of knowledge of waste treatment. Therefore, this study aims to find out the implementation of Urban Planning and Regional Planning of Semarang city as well as the driving factors and inhibiting factors faced by Semarang City Government in implementing Urban Plans and Regional Plans of Semarang City. Analytical techniques to obtain data through interviews with informants, observation, and supporting documents. This research uses the theory of George Edwards III (1980) can be seen that the implementation of the policy is influenced by four factors such as: communication, resources, position and bureaucratic structure. The results of this study indicate that the Implementation of Spatial Planning and Regional Planning of Semarang city seen from